Жанрово-стильова специфіка кримськотатарської епічної оповіді «Арзи й Гамбер» - Гуменюк, О.М. (Культура народов Причерноморья, 2014)
Кримськотатарські епічні оповіді – дестани – можна поділити на два основні різновиди. Одна група дестанів пов’язана з художнім осягненням історичних, суспільно-політичних процесів. Інша група – це любовні історії. Тут попри провідну епічну оповідність доволі відчутний ліричний струмінь, а героїчні мотиви поєднуються із сентиментальними. Характерним зразком романтичної епічної оповіді є дестан «Арзи й Гамбер», котрий є основним об’єктом розгляду в цій статті. Звертається увага на тематичні й жанрово-стильові аспекти цього фольклорного твору. Несприятливим життєвим обставинам протиставляється сила почуттів закоханих, здатна долати тяжкі випробування і навіть смерть. Крымскотатарские эпические сказания – дестаны – можно поделить на две основных разновидности. Одна их группа связана с художественным постижением исторических, социально- политических процессов. Другая группа – это любовные истории. В последней, хоть и преобладает эпическая повествовательность, явственно ощутима лирическая струя, а героические мотивы сочетаются с мотивами сентиментальными. Характерный образец романтического сказания – дестан «Арзы и Гамбер», являющийся основным объектом рассмотрения в данной статье. Обращается внимание на тематические и жанрово-стилевые аспекты этого фольклорного произведения. Неблагоприятным жизненным обстоятельствам противопоставляется сила чувств пылко влюбленных, способная превозмогать тяжкие испытания и даже смерть. Crimean Tatar epic narrative – destan – can be divided into two main types. One group of destans are connected with the artistic comprehension of the historical, social and political processes. Another ones are love stories. In spite of leading the epic tale significant lyrical stream and heroic motifs combined with sentimental features. The peculiar of prose narrative and poetic passages are combined in narrative the structure of destan. The main part of the story of the heroic destan, which is shared with the social and political processes, has a poetic form as the speech of the characters; the prose passages are only connecting transitive parts of the narrative type. In a heroic and romantic destan or just a romantic nature of destan, which are compared with the works of the first type is of more recent origin, the narrative is entirely in prose form, and the poetic parts contain words or songs of heroes. A typical example of the romantic epic story is "Arzy and Gamber", which is the main object of consideration in this article. There is payed attention to thematic, genre and stylistic aspects of this folklore. The dramatic circumstances are contrasted with feelings of enamored which can overcome the difficulties of life and even death.